EVALUATING ACETONE AND METHANOL FOR ELECTROPHORETIC DEPOSITION OF SS 316L COATED WITH HYDROXYAPATITE/MULTIWALLED CARBON NANOTUBES DENTAL IMPLANTS: A FOCUS ON CORROSION RESISTANCE - Valmelina, Ersyi Arini; Wulan, Praswasti Pembangun Dyah Kencana; Whulanza, Yudan; Adin, Mehmet Şükrü (Jurnal Kimia Riset, 2024)
Dental implants offer a reliable solution for replacing damaged tooth roots. This research investigates the comparative performance of acetone and methanol as suspension media in the fabrication of stainless steel type 316L-based dental implants using the Electrophoretic Deposition (EPD) method, a technique known for its simplicity and cost-effectiveness. Voltage variations of 20V, 30V, and 40V were applied to both acetone and methanol suspensions for a duration of 20 minutes. The morphology of the Hydroxyapatite/Multiwalled Carbon Nanotube (HA/MWCNT) coatings was meticulously characterized using Scanning Electron Microscopy (SEM). Corrosion resistance was evaluated through Potentiodynamic Polarization (PDP) and Electrochemical Impedance Spectroscopy (EIS) techniques. Remarkably, at 30V, a homogeneous and crack-free coating was achieved, demonstrating superior corrosion resistance. This was further corroborated by the resistance values of 23.891 Î© and 114.990 Î© for the acetone and methanol samples, respectively. Additionally, the corrosion rates of 0.075 (mmpy) and 0.0004 (mmpy) for the acetone and methanol samples further emphasized the superiority of methanol as a suspension medium. These findings unequivocally establish methanol as the optimal choice for achieving superior deposition quality and corrosion resistance in the context of the EPD method for stainless steel type 316L-based dental implants.